Extracorporeal Membrane Oxygenation Utilization in Blunt and Penetrating Traumatic Injuries: A Systematic Review. Issue 11 (November 2022) - Ehrlich, Haley; Bisbee, Charlie; Ali, Aleeza; Fanfan, Dino; Gill, Sabrina; McKenney, Mark; Elkbuli, Adel
Background: Extracorporeal membrane oxygenation (ECMO) has become an increasingly used treatment modality for severe respiratory insufficiency in trauma patients. Examining ECMO use specifically in blunt and penetrating traumas can aid in directing future protocols. We aim to evaluate the outcomes of ECMO use in both blunt and penetrating trauma patients through a systematic review of current literature. Methods: An online search of 2 databases (PubMed and Google Scholar) was performed to analyze studies, which evaluated the use of ECMO in blunt and penetrating traumas. Preferred Reporting Items for Systematic Reviews and Meta-Analysis and Grading of Recommendations Assessment, Development and Evaluation guidelines were followed. Data extracted included mechanism of injury, injury severity scores (ISSs), complications, and mortality rates. Results: The search demonstrated 9 studies that met our review inclusion criteria. A total of 207 patients were included, of which 64 (30.9%) were non-survivors and 143 (69.1%) were survivors. There was a total of 201 blunt traumas with 61 (30.3%) deaths, whereas penetrating traumas had 2 deaths (33.3%) out of 6 total patients. Complications reported included acute renal failure, hemorrhage at the cannula site, and transient neurological deficits. Most studies found better survival rates and less complications in younger patients and those with lower ISS. Conclusion: Expanding the use of ECMO to include blunt and penetrating trauma patients provides the trauma surgeons with another crucial potentially lifesaving tool with an overall survival rate of 70%. Anticipating increased future use of ECMO in blunt and penetrating trauma patients, distinct protocols ought to be instilled to better address the care needed for these critically ill trauma patients.